Cassiterite U-Pb dating and micro-XRF analysis constraint on the formation of Xinlu Sn-Zn deposit, South China - Xiao, Chang-Hao; Yu, Ping-Ping; Liu, Xiao-Hu; Liu, Xiang-Chong; Tang, Yan-Wen; Wang, Wen-Lei; Zhang, Yu (Frontiers in Earth Science, 2023)
This study presents rock slab and thin section reflection mapping, element mapping by Micro-XRF (μ-XRF) analysis, and in situ cassiterite U-Pb laser ablation-inductively coupled plasma mass spectrometer (LA-ICP-MS) ages of the Xinlu Sn-Zn deposit, Nanling Sn-W belt, South China. The new results provided constraints on the age and processes of Sn mineralization and thus further discussed the role of the Paleo-Pacific plate in the formation of Sn-W mineralization in the Nanling Sn-W belt. Based on mineralogy and μ-XRF analysis, four mineralization episodes are distinguished in the Baimianshan segment, Xinlu deposit, including (I) prograde skarn stage characterized by the mineral assemblages of garnet, pyroxene, marble, hornfels; (II) retrograde skarn-sulfide composed of massive pyrrhotite, sphalerite with parts of epidote, cassiterite; (III) quartz sulfide vein stage consisting of arsenopyrite, pyrite, quartz, and (IV) barren calcite crosscutting the former episodes. The time of retrograde skarn-sulfide mineralization is dated by LA-ICP-MS cassiterite U-Pb at 168.7 ± 1.3 Ma. These U-Pb ages, combined with previous geochronological studies, support a Sn mineralization event associated with the 159.5–168.7 Ma magmatism in the Guposhan-Huashan district. The Xinlu Sn-Zn mineralization and the Middle-Late Jurassic Sn-W mineralization in the Nanling belt, South China is genetically related to asthenospheric upwelling and crust-mantle interaction caused by the subduction of the Paleo-Pacific plate. Our results demonstrate that thin section reflection and μ-XRF element mapping are powerful tools for determining paragenesis in ore deposits and are highly effective to guide the selection of analytical positions for cassiterite U-Pb dating. This method may also be applicable to in-situ geochronology of other minerals.